2006
DOI: 10.1266/ggs.81.103
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of DNA variation in natural populations of two related conifers, Cryptomeria japonica and Taxodium distichum (Cupressaceae sensu lato)

Abstract: We investigated DNA variation within and between two closely related conifers, Cryptomeria japonica and Taxodium distichum, at nuclear loci encoding ferredoxin, glutamyl-tRNA reductase, lycopene beta cyclase, and phosphoribosylanthranilate transferase. Average nucleotide diversity at silent sites was estimated to be 0.0035 (SE 0.0012) in C. japonica and 0.0058 (SE 0.0006) in T. distichum . One population in C. japonica was differentiated from the others but generally there was not much differentiation among po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…For example, using this test, Smith and EyreWalker (2002) found that rates of replacement substitution were higher than expected across loci in Drosophila and estimated that 45% of replacement substitutions were due to positive selection. In our study, a higher than expected frequency of replacement polymorphism was found at the CC2188 locus, and a similar pattern has been found at the Lcyb locus in a previous study (Kado et al 2006). However, these patterns can be more readily explained by substitutions with nearly neutral variants at replacement sites (Ohta 1992) rather than positive selection.…”
Section: Divergence Between Sugi and Hinokisupporting
confidence: 92%
See 3 more Smart Citations
“…For example, using this test, Smith and EyreWalker (2002) found that rates of replacement substitution were higher than expected across loci in Drosophila and estimated that 45% of replacement substitutions were due to positive selection. In our study, a higher than expected frequency of replacement polymorphism was found at the CC2188 locus, and a similar pattern has been found at the Lcyb locus in a previous study (Kado et al 2006). However, these patterns can be more readily explained by substitutions with nearly neutral variants at replacement sites (Ohta 1992) rather than positive selection.…”
Section: Divergence Between Sugi and Hinokisupporting
confidence: 92%
“…Notably, cypress tends to have higher than expected frequencies of singleton polymorphisms (Kado et al 2006), and hinoki tends to have relatively small numbers of alleles (this study). These patterns seem to reflect differences in historical population structures among the species rather than differences in the effects of natural selection on them.…”
Section: Deviation From the Standard Neutral Model In Hinokimentioning
confidence: 52%
See 2 more Smart Citations